If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1(2x + -4) = 3(3x + -7) Reorder the terms: 4 + -1(-4 + 2x) = 3(3x + -7) 4 + (-4 * -1 + 2x * -1) = 3(3x + -7) 4 + (4 + -2x) = 3(3x + -7) Combine like terms: 4 + 4 = 8 8 + -2x = 3(3x + -7) Reorder the terms: 8 + -2x = 3(-7 + 3x) 8 + -2x = (-7 * 3 + 3x * 3) 8 + -2x = (-21 + 9x) Solving 8 + -2x = -21 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 8 + -2x + -9x = -21 + 9x + -9x Combine like terms: -2x + -9x = -11x 8 + -11x = -21 + 9x + -9x Combine like terms: 9x + -9x = 0 8 + -11x = -21 + 0 8 + -11x = -21 Add '-8' to each side of the equation. 8 + -8 + -11x = -21 + -8 Combine like terms: 8 + -8 = 0 0 + -11x = -21 + -8 -11x = -21 + -8 Combine like terms: -21 + -8 = -29 -11x = -29 Divide each side by '-11'. x = 2.636363636 Simplifying x = 2.636363636
| 35/6-5/6:2/3= | | 5x+2y+0.5z=100 | | (-10)+3-24:4-(-5)= | | (4x+12/5)(15t/3x+9) | | 11/18+11/18 | | a+2=2b | | Y=-5x-80 | | -2x+3y=5 | | ln(2x+3)*ln(x^2)=0 | | 7y-2.75=0.5 | | 5*7*11*13= | | (9x-4)=(3x+2) | | y-3=5(x+1) | | (3a-7)(4a+5)= | | y-2=.4(x-3) | | 4y-1.9=6.3 | | 4y-19=6.3 | | m+9=3(m-5)+7 | | -4=3.5-1.5y | | 8m=5m+1 | | 5x+7=-3x-5 | | 4x^4+19x^2-5x+3=0 | | x=8x-50 | | 2(2y-3)=9-2y | | y=.50x-3 | | 3x-8y=27 | | (x^2+8x-7)(9x^2-8x+8)= | | x+2x=880000 | | .33-.03(x+1)=-.05(2-x) | | 2/3n-n/6 | | 4x^3-12x=1 | | 5x^3-2x^2-15x+6= |